Additive effects of acupuncture in alleviating anxiety: A double-blind, three-arm, randomized clinical trial. (November 2021) - Sabbagh Gol, Ali; Rezaei Ardani, Amir; Farahmand, Seyed Kazem; Dadgarmoghaddam, Malihe; Ghorani, Vahideh; Rezaei, Shima; Khorsand, Ali
Abstract: Background: In this trial, additive effects of acupuncture to selective serotonin reuptake inhibitors (SSRIs) treatment for reducing anxiety, were investigated. Methods: 112 patients with anxiety disorder were randomly divided into three groups including SSRIs alone (drug group), SSRIs with sham acupuncture (control group) and SSRI with acupuncture (acupuncture group), and treated for 4 weeks. At the beginning of the study and on day 28, Spielberger State-Trait Anxiety Inventory (STAI) questionnaire was completed and serum levels of cortisol were measured. Results: 105 patients completed the treatment period. STAI score showed significant differences among the three groups at the end of the study; importantly, changes in STAI score in the acupuncture group were significantly larger than the other groups. A decrease in cortisol levels was observed in all groups; though statistically non-significant, this decrease in the acupuncture group was larger. Conclusion: Acupuncture combined with SSRIs can significantly improve anxiety state compared to anti-anxiety therapy using SSRIs alone. Highlights: This trial evaluated additive effects of 4-week acupuncture therapy on anxiety. The acupuncture group had significantly larger changes in STAI score. Cortisol level in all groups was decreased non-significantly. Acupuncture + SSRIs significantly improved anxiety state compared to SSRIs alone.